PrEP uptake and delivery setting preferences among clients visiting six healthcare facilities in Eswatini - Maxime Inghels; Hae-Young Kim; Frank Tanser; Anita Hettema; Shannon A. McMahon; Catherine E. Oldenburg; Sindy Matse; Stefan Kohler; Pascal Geldsetzer; Till Bärnighausen (My University, 2022)
Due to the high HIV incidence among the general population of Eswatini, pre-exposure prophylaxis (PrEP) for HIVexposed individuals is recommended. However, little is known about PrEP uptake and preferences in PrEP delivery healthcare setting among the general population. We conducted a secondary analysis of a randomized trial that aimed to increase PrEP uptake. All clients eligible for PrEP in one of six public-sector healthcare facilities in Eswatini were included. PrEP uptake was stratifed by initial reason for visit (e.g. outpatient). Preferences in PrEP delivery setting were collected among those clients who initiated PrEP. A total of 1782 clients had their HIV acquisition risk assessed. Of these, 72% (1277/1782) were considered at risk by healthcare providers and, among them, 40% (517/1277) initiated PrEP. Uptake was higher among clients visiting specifcally to initiate PrEP (93%), followed by HIV testing visits (45.8%) and outpatient visits (40%). Among those who initiated PrEP, preferred delivery settings were outpatient services (31%), HIV testing services (26%), family planning (21%) and antenatal services (14%). Men or those at high risk of HIV acquisition were more likely to prefer HIV testing and outpatient services, while young women were more likely to visit and express a preference for antenatal and family planning services. Outpatient services and HIV testing services could be preferable choices for PrEP delivery integration, due to the high PrEP uptake and delivery setting preferences of the populations who use these services. Antenatal and family planning could also be considered with a view to targeting the youngest women.
Keywords: Pre-Exposure Prophylaxis · HIV · Consumer preference · Health services · Eswatini